The Universality of Traditional Tales of the Portuguese Speaking Countries - M.Margarida Pereira-Müller 177152 (Journal of Global Initiatives, 2016)
Throughout the ages, the traditional tale has been the vehicle used for transmitting the culture from generation to generation - the memory of a community. Since the beginning of mankind there have always been tales in all countries and in all cultures of the world. Many of the traditional stories we think are Portuguese or European are to be found as well in other parts of the world, told in a very similar way. Sometimes the only difference is the physical frame: the landscape, the flora and the fauna, how people dress or eat.